Advanced non-Small cell lung cancer patients at the extremes of age in the era of epidermal growth factor receptor tyrosine kinase inhibitors. (August 2016) - Chen, Yu-Mu; Lai, Chien-Hao; Rau, Kun-Ming; Huang, Cheng-Hua; Chang, Huang-Chih; Chao, Tung-Ying; Tseng, Chia-Cheng; Fang, Wen-Feng; Chen, Yung-Che; Chung, Yu-Hsiu; Wang, Yi-Hsi; Su, Mao-Chang; et al.
Highlights: Very old NSCLC patients had a lower BMI and poor ECOG PS. EGFR mutations reverse the poor prognosis of very old patients with NSCLC. Young NSCLC patients had a lower BMI, more brain and bone metastases. Young lung cancer patients have a poor prognosis even if they harbor EGFR mutations. Abstract: Objectives: The clinical characteristics and survival of very young (≤40 years) and very old ( > 80 years) patients with advanced non-small cell lung cancer (NSCLC) are distinct. However, the benefits of epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) to patients at the extremes of age with NSCLC harboring EGFR mutation have not been well studied. We retrospectively studied the effect of extreme age on patients' clinical characteristics and prognosis. Materials and methods: Of 1510 lung cancer patients diagnosed between November 2010 and March 2014, 555 patients who were tested for EGFR mutations were included. Patients were divided into the following groups according to age: young (≤40 years), lower medium (41–60 years), higher medium (61–80 years), and very old (>80 years). Results: Of the 555 patients, 20 (3.6%) patients were aged ≤40 years and 60 (10.8%) patients were aged >80 years. Young NSCLC patients had a lower BMI (p = 0.003), more brain (p = 0.016) and bone metastases (p = 0.002) Very young lung cancer patients still have poor prognosis even they were EGFR mutant. (EGFR mutant vs. wild type patients, OS: 12 vs. 7.3 months, p = 0.215) Very old NSCLC patients had a lower BMI (p = 0.003) and poor ECOG PS (p = 0.028). Positive EGFR mutation test reverses poor prognosis of elderly NSCLC patients. (EGFR mutant vs. wild type patients, OS: 13.2 vs. 4.9 months, p = 0.003) Conclusion: We observed EGFR mutations reverse the poor prognosis of old patients with NSCLC. However, young patients with lung cancer have a poor prognosis even if they harbor EGFR mutations.